Money Market Development and the Demand for Money: Some Preliminary Evidence - Cohen, Bruce C. (Journal of Financial and Quantitative Analysis, 1971)
George Kaufman and Cynthia Latta in “The Demand for Money: Preliminary Evidence from Industrial Countries, ” have presented econometric evidence that the money-demand function may shift with the development of financial markets. The thesis depends on the heightened cross-elasticities and lowered wealth-elasticities (or income-elasticities) that are supposed to attend the development of new near-money forms. Their evidence is based on a summary of statistics from money-demand equations for developed and less-developed countries.